Kebijakan Bailout Century: Diskresi Atau Kriminalisasi Kebijakan - Sitorus, Lily Evelina (UI Scholars Hub, 2016)
Century bailout policy is the government's discretion. However, when there is resistance in the Parliament, this policy is a problem that until now has not as well satisfy the parties. On the other hand, the economic crisis is a reality that is happening in the community. Government as the policy makers feel they have the authority as stipulated in the legislation in force. Therefore, the decision to prosecute government policy is regarded as a form of criminalization policies. This study tried to find a middle ground on the issue. The standpoint of administrative law is used as an analysis in finding the right solution. It was with the aim of no longer controversial policies issued by the government is considered to be detrimental to the country's financial and creating legal certainty in the implementation.